Biooxidation of refractory silver minerals as pretreatment for silver recovery - Arias Arce, Vladimir Alejandro (2023)
The worldwide demand for silver is increasing due to the technological development in different areas, especially for the requirements in the production of renewable energies; therefore, for the treatment of refractory minerals by conventional processes, it is necessary to study mechanisms to identify the viability of their processing and the feasibility of their recovery, ensuring profitability. Gold and silver present in the matrix of sulfide-based ores are not affordably recovered by the conventional method involving leaching in sodium cyanide solution. Therefore, it must be subjected to oxidation pretreatment or conversion of the sulfides to simple compounds that allow recovery of the precious metals. The methods of oxidation of minerals considered refractory are carried out by hydro and pyrometallurgical methods, seeking the dissolution of sulfur, iron, arsenic and other elements present. It is important to identify and consider the mineralogical structure, microbiological variety, physicochemical characteristics, types of reactors, bacterial interactions, among other factors. The choice of biooxidation as the preferred process in projects for the recovery of gold, silver, copper or other metals, in most cases is based on the economic advantage, compared to the conventional processes of roasting, chemical leaching and pressurized leaching. The biooxidation of refractory argentiferous ores has been extensively studied in recent years, concluding that its application is feasible, mainly because it is environmentally friendly.